The Impact of Personal And Environmental Factors Through Experience Characteristics on Entrepreneurial Performance in Indonesian Start-Ups - Danil, Lilian; Jahroh, Siti; Syarief, Rizal; Taryana, Asep (School of Business, IPB University (SB-IPB), 2025)
Background: Entrepreneurial performance is essential for start-ups' development, particularly the ability to transition smoothly from experimentation to scaling. Start-ups' performance in Indonesia remains challenging in that the failure rate is up to 90% within the first five years.Purpose: This study aims to assess the direct influence of personal and environmental factors through experience characteristics on entrepreneurial performance in start-ups in Indonesia and the indirect influence of these factors through experience characteristics on entrepreneurial performance.Design/methodology/approach: This study employed a quantitative approach, applying Partial Least Squares Structural Equation Modelling to analyze data collected from questionnaires distributed to 268 start-ups in Indonesia.Finding/Results: The results indicated that personal and environmental factors significantly enhance experience characteristics and entrepreneurial performance. This study also found that personal and environmental factors through experience characteristics significantly enhance entrepreneurial performance in Indonesian start-ups.Conclusion: This study evaluated how experience characteristics as a mediator strengthen the impact of personal factors on entrepreneurial performance and weaken the impact of environmental factors on entrepreneurial performance. This research possesses academic and managerial implications, particularly for advancing scientific progress in entrepreneurial performance models in start-ups in Indonesia.Originality/value (State of the art): Start-ups must enhance their entrepreneurial performance by focusing on personal factors, including entrepreneurial education and passion, as well as environmental factors like developing a more dynamic entrepreneurial ecosystem, improving marketing techniques, and aligning with global market demand. Keywords: business, entrepreneurial ecosystem, entrepreneurial education, entrepreneurship environment, start-ups' development